PENERAPAN PSAK NO. 45 TENTANG PELAPORAN KEUANGAN ORGANISASI NIRLABA PADA SANGGAR SENI BUDAYA LOGOS MA’KANTAR - Korompis, Claudia W.M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Global economic development could not be separated from the role of an organization of profit and non-profit organizations. Non-profit organizations (non-profit) into a container made of human resources as the most valuable asset. Although it is not concentrated on profits, but the financial reporting presented by this organization must have a standard as a basis for the preparation and reporting to interested parties. SFAS No. 45 states that non-profit organizations to obtain resources from the donations of members and other contributors do not expect any compensation from the organization. The objective of financial statements for internal parties is to know the financial situation that exists in the organization, while external parties aimed to determine whether the available funds have been used properly and in the attached financial statements of the organization. The study was conducted at the Cultural Arts Studio Logos Ma'kantar. This study aims to look at how the financial statements Cultural Arts Studio Logos Makantar whether in accordance with SFAS No. 45.Metode analysis used is descriptive qualitative method outlines the nature, describing, comparing a data.Hasil and conclusions of this study are the financial statements of Studio Art culture Logos Makantar not prepare financial statements in accordance with the format of the financial statements of a non-profit that exists in SFAS No. 45, and this makes the board are encouraged to immediately apply the financial statements in accordance with SFAS No. 45 for the benefit of the organization in the future.